1989
DOI: 10.1111/j.1745-6592.1989.tb01142.x
|View full text |Cite
|
Sign up to set email alerts
|

A Tracer Test for Detecting Cross Contamination Along a Monitoring Well Column

Abstract: A tracer test was used to evaluate whether cross contamination exists along a monitoring well completed through a shallow ground water system in fractured clay and screened in a sand and gravel aquifer. The fractured clay is separated from the sand and gravel deposit by a layer of highly plastic unfractured clay. A natural vertical downward hydraulic gradient of approximately 0.5 exists between the shallow system and the sand and gravel aquifer. Ground water contamination was detected in an adjacent monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Tests can be conducted between screens or sampler ports to evaluate the effectiveness of seals. Possible tests include pumping one screened interval and measuring the hydraulic response in another, or injecting a tracer in one screened interval and searching for the presence of that tracer in other intervals (Meiri, 1989;LeBlanc and others, 1991).…”
Section: Screened Open-hole and Multilevel Designsmentioning
confidence: 99%
“…Tests can be conducted between screens or sampler ports to evaluate the effectiveness of seals. Possible tests include pumping one screened interval and measuring the hydraulic response in another, or injecting a tracer in one screened interval and searching for the presence of that tracer in other intervals (Meiri, 1989;LeBlanc and others, 1991).…”
Section: Screened Open-hole and Multilevel Designsmentioning
confidence: 99%
“…Detection and analysis of hydraulic short‐circuits has been well documented in the literature. Meiri (1989), for example, showed that cross contamination between two aquifers may be detected by a simple tracer test. His detection method examines the chemical impact of a hydraulic short‐circuit but is only qualitative and does not determine the leakage rate.…”
Section: Introductionmentioning
confidence: 99%
“…For field conditions, detection and evaluation methods should be simple and should yield reasonably accurate material characteristics. Although Meiri (1989), Chapuis and Sabourin (1989), and Chapuis and Chenaf (1998) provide useful detection methods, there is as yet no known method to evaluate the hydraulic properties of a defect and to determine its flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…When a riser (also commonly called a well casing) is placed in a borehole, an annular space is cre ated between the riser and the sur rounding soil. If not properly sealed, the annular space can be a potential pathway for transport of contami nants in the subsurface (Meiri 1989;Pekarun 1995;Lacombe et al 1995;Pankow and Cherry 1996). Con tamination can occur due to mixing of adjacent bodies of clean and con taminated ground water or from intrusion of contaminated surface water (Riewe 1996).…”
Section: Introductionmentioning
confidence: 99%